First-time versus repeat visitors: the Volksblad Arts Festival - Martinette Kruger; Melville Saayman; Albert Strydom (Acta Academica, 2010)
This article focuses on the differences and/or similarities between first-time and repeat visitors at the Volksblad Arts Festival as an alternate approach to market segmentation. The research was conducted by means of a visitor survey, during which 397 questionnaires were administered. Two-way frequency tables and chi-square tests were used to compare first-time and repeat visitors based on socio-demographics, behavioural characteristics, overall satisfaction with the festival and the type of shows/productions attended. The results indicate differences that could affect the sustainability and future of the festival. These differences should be considered as determinants when the festival programme is designed and marketed.